Geometric capture and escape of a microswimmer colliding with an obstacle. Issue 17 (7th May 2015) - Spagnolie, Saverio E.; Moreno-Flores, Gregorio R.; Bartolo, Denis; Lauga, Eric
<x xml:space="preserve">Abstract</x> A colloid larger than a critical size may act as a passive trap for microswimmers. We address the critical trapping radius, the basin of attraction, the scattering angle for sub-critical colloid sizes, and the effects of Brownian fluctuations.